Complete mitochondrial genome of Acanthopsyche nigraplaga (Lepidoptera: Psychidae). Issue 3 (4th March 2021) - Lee, Keon Hee; Kim, Min Jee; Wang, Ah Rha; Park, Jeong Sun; Kim, Sung-Soo; Kim, Iksoo
Abstract: We report the mitochondrial genome (mitogenome) of a case-making moth Acanthopsyche nigraplaga Wileman, 1911 (Lepidoptera: Psychidae). The 15, 704 bp long complete mitogenome comprises a typical set of genes [13 protein-coding genes (PCGs), 2 rRNA genes, and 22 tRNA genes] and one major non-coding, A + T-rich region, with an arrangement identical to that observed in most lepidopteran mitogenomes. Twelve of the 13 PCGs of the A. nigraplaga mitogenome initiate with a typical ATN start codon, however COI contains the atypical CGA start codon that is common for lepidopteran COI genes. A phylogenetic analysis using concatenated nucleotide sequences of the 13 PCGs and 2 rRNA genes using the Bayesian inference method fully resolved A. nigraplaga in a monophyletic clade within the Psychidae. Acanthopsyche nigraplaga was situated in a sister position to Eumeta variegata and Mahasena oolona with high nodal support. As more mitogenome sequences are available further scrutinized analysis for the superfamily Tineoidea including Psychidae will be possible.